mRNA expression of chemosensitivity genes as a predictor of response to neoadjuvant chemotherapy in non-small cell lung cancer - M. M. Tsyganov; I. V. Deryusheva; E. O. Rodionov; L. A. Efteev; S. V. Miller; M. K. Ibragimova; E. E. Perminova; O. V. Cheremisina; I. G. Frolova; S. A. Tuzikov; N. V. Litviakov (Сибирский онкологический журнал, 2019)
The objective response rate to neoadjuvant chemotherapy (NAC) in patients with non-small cell lung cancer (NSCLC) is approximately 16 %. Therefore, the search for new predictive factors and markers that could precisely predict the NAC response and be relevant to the choice of the adequate treatment policy is of utmost importance. the purpose of the study was to analyze the relationship between the expression levels of chemosensitivity genes and NAC response in patients with non-small cell lung cancer. material and methods. The study included 30 patients with stage IIAIIIB NSCLC. Total RNA was isolated from normal and tumor lung tissue samples prior to NAC. The expression level of chemosensitivity genes, such as BRCA1, RRM1, ERCC1, TOP1, TOP2a, TUBB3, TYMS, and GSTP1 was evaluated by real-time reverse transcriptase quantitative PCR (RT-qPCR). results. A significant difference in the expression levels of the studied genes between patients with different NAC response was found. The objective response to therapy was observed in 67 % (10/15) of patients having no ERCC1 expression compared to those with ERCC1 expression (p<0.05). Low (less than 0.2) and high (more than 1.2) BRCA1 expression levels were associated with low rates of NAC response compared with patients whose expression level was between the lower and upper quartiles. Statistically significant differences were shown for the GSTP1 and RRM1 genes. conclusion. A comprehensive assessment of the expression of chemosensitivity genes is important not only in terms of understanding heterogeneity and complexity of the molecular biology of NSCLC, but also for more accurate prediction of response to NAC and identification of potential drug targets.